The ethics of diversity, equity, inclusion, and justice in the earth system sciences - Burt, Melissa A.; Haacker, Rebecca; Montaño, Patricia; Vara, Marissa; Sloan, Valerie (Frontiers in Physics, 2022)
Institutions’ motivations for pursuing diversity, equity, inclusion and justice (DEIJ) often center on the benefits to the organization, an argument known as the business case for diversity in which diverse teams are more creative, set high bars for research, and produce ideas that are more innovative than those produced by homogeneous groups. As the sole motivation for DEIJ efforts, the business case is flawed and does not address the harmful workplaces many marginalized scholars encounter. Institutions can make more progress towards diversifying the STEM workforce by acknowledging the ethical responsibilities for doing so and transitioning to an equity-centered approach. Emphasizing personal motivations to actively engage in DEIJ work resonates with individuals more, rather than engaging with DEIJ to benefit an institution’s goals. Two recent studies support this argument. The first is an alumni survey and focus groups of postdoctoral fellows in the Advanced Studies Program at the National Center for Atmospheric Research to explore alumni efforts and motivations for engaging in DEIJ work. The second study surveyed attitudes towards DEIJ efforts among STEM graduate students at Colorado State University who took a course on social responsibility in science. Both studies show the motivations for scientists to support and get involved in these efforts and indicate that the business case is misaligned with the motivations of students and professionals in STEM. Understanding the attitudes and motivations that individuals have for DEIJ in STEM presents an opportunity for how institutions can best learn from and support these motivations for systemic change.